La influencia de los árboles en el microclima en un paseo peatonal de la ciudad de Talca (Chile) - Martínez Toledo, Ricardo (2023)
Thermal behavior was assessed through a causal relationship between four climatic variables: temperature, relative humidity, wind speed at 1.5 m, the temperature at ground level (0.05 m) and the presence of trees in a renovated pedestrian promenade. The measurements were collected in this area during the summer season, distributed in four Blocks (block I, II and III corresponding to renovated streets and block IV not renovated streets) in three daily schedules, generating 3,108 records. The statistical analysis showed a high dispersion, however, the Block III showed significant differences in both temperature and relative humidity, showing that urban trees cannot generate a mitigating effect in this renovated urban environment. In Blocks I and II, a decrease in temperatures was observed in schedule 2. Due to the differences found in the temperature and relative humidity records on the different measuring days, an unfavorable condition of environmental comfort was identified in Block III. This could be due to the section represented by this Block and the construction material used, along with a scarce green infrastructure. It is suggested that in future renovations, the type of construction material to be used on the surface should be previously evaluated, also promoting a green infrastructure  to mitigate these effects during the summer.